Thermal energy storage with phase change materials : a literature review of applications for buildings materials /: a literature review of applications for buildings materials. ([2019]) - Delgado, João M. P. Q; Martinho, Joana C; Sá, Ana Vaz; Guimarães, Ana S; Abrantes, Vitor
No abstract available